Persepsi Remaja di SMA Veteran Purwokerto mengenai Traficking - sri pangestuti (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2011)
Trafficking is not a new phenomenon, and a hidden problem which difficult to find the real numberof victims. That’s what the basis for the writer to research on Veteran’s Senior High SchoolPerceptions About Trafficking.The purpose of this study is to inestigate student’s of Veteran’s Senior High SchoolPerceptions in Purwokerto, about traffing, and also the media used by the student in accessinginformation about trafficking.The metodology used in this research is qualitative descriptive, withaccidental technique for information election, whith the data collection throughResults show that students of the Vteran’s Senior High School in Purwokerto Perceptionsabout traffcking are : firstly, trafficking is various forms such as child traffing, exploitation ofwomen for sex, slavery, etc., is a problem thai must be resolved. The most vulnerable groups ofsociety who become victims of trafficking are children and women, so providing protections andskill for victims of trafficking need to be done so these groups do not become victims again.Handling of trafficking cases were deemed not satisfactory requires effort and attention seriouslyfrom all stackeholders. One of the most effective ways ays to provide a punishment as servere ason the propetrators, so hopefully will not happen again.On the other hand, mass media, such astelevision, the radio, newspaper, magaziens were becomes a refference for informations to find outnews about trafficking.